Performance enhancement of double hard limited 2D atmospheric OCDMA system using aperture averaging and spatial diversity. Issue 5 (1st March 2019) - Yadav, Ajay; Kar, Subrat; Jain, Virander Kumar
Abstract : The probability of error of a new two‐dimensional (2D) code, one‐coincidence frequency hopping code/quadratic congruence code, atmospheric optical code division multiple access (OCDMA) system is evaluated with single hard limiter and double hard limiter in presence of weak, moderate and strong turbulence. In the atmospheric channel, weak turbulence is characterised by lognormal probability density function (pdf) and moderate and strong turbulence by gamma‐gamma pdf. Further, aperture averaging and spatial diversity techniques are used to improve the error probability ( P e ) of double hard limited 2D atmospheric OCDMA system. The increment in the receiver aperture diameter from 2 to 10 cm improves performance in presence of weak, moderate and strong turbulence. This improvement in performance is due to aperture averaging. In addition, spatial diversity also improves performance in presence of turbulence and different weather conditions, i.e. light fog, light mist, haze and clear air. For an eight user system, P e = 10 − 6 is achievable with light mist, haze and clear air in presence of weak, moderate and strong turbulence. With light fog, eight users can communicate (can achieve P e = 10 − 6 ) in presence of weak turbulence and not in moderate and strong turbulence.